The changing face of cosmetic surgery regulation: a review of controversies and potential reforms. Issue 5 (26th March 2022) - Jobson, Dale; Freckelton, Ian
Abstract: Cosmetic surgery is becoming increasingly popular in Australia with the industry estimated to be worth over 1 billion dollars annually. Regulators both in Australia and internationally have been criticized for not keeping up with the rapidly changing field and keeping patients sufficiently safe in an environment that is problematically entrepreneurial. In this article, we explore the current regulation of and controversies surrounding cosmetic surgery in Australia, including the use of the title 'cosmetic surgeon', consent processes and the phenomenon of medical tourism. Lastly, we review the potential future reforms in Australia and how other countries have regulated the industry to keep patients safe.